Islamisasi Makassar Abad 17; Kajian tentang HUbungan Umara dan Ulama Nusantara - Damopoli, Mulyono (Buletin Al-Turas, 2005)
Abstract; Arrival event of three Moslem scholars from Malay Empire in early seventeenth century to Makassar can be attested how close relationship between among Moslem scholarand umara in the Indonesian Archipelago at the time. In the context of Islamization of Makassar in the seventeenth century, relation of umara of Makassar Empire with umara from other Moslem empires such as Demak, Banten, monarchic of Malay Moslem in Aceh, Malacca, and Johor can be classified as very strong.